2021
DOI: 10.22146/jcoemph.61647
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of e-SEKOCI (The Online Class of Sekolah Komplementer Cinta Ibu) in counselling midwives and pregnant women during COVID-19 pandemic

Abstract: Pregnancy classes are vital for successful communication, information, and health education in maternity services. However, their implementation should be postponed during the COVID-19 pandemic to prevent COVID-19 transmission in pregnant women who are classified as a vulnerable group, especially if they had a history of pregnancy with non-communicable diseases. Therefore, we implemented e-SEKOCI (The Online Class of Sekolah Komplementer Cinta Ibu) which aimed to provide counselling and mentoring of pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Scientific evidence supports the benefits of complementary therapy in supporting midwifery services, both in promotion and prevention but also curatively and rehabilitatively (Nurfatimah, 2021). The critical and conceptual approach used in this study emphasizes creative efforts that aim to produce a problem-solving approach model to become a framework for regulating and implementing complementary midwifery services (Setyani, 2021).…”
Section: Introductionmentioning
confidence: 78%
“…Scientific evidence supports the benefits of complementary therapy in supporting midwifery services, both in promotion and prevention but also curatively and rehabilitatively (Nurfatimah, 2021). The critical and conceptual approach used in this study emphasizes creative efforts that aim to produce a problem-solving approach model to become a framework for regulating and implementing complementary midwifery services (Setyani, 2021).…”
Section: Introductionmentioning
confidence: 78%
“…Retrospectively, a literature review revealed that midwives worldwide have converted in-person antenatal classes or breastfeeding support to innovative internet-based sessions during the pandemic [5,9,[19][20][21][22][23]. This highlights the importance of antenatal classes and midwives' urge to support pregnant women, especially in adverse circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 virus is increasingly spreading and experiencing an increase in deaths in pregnant women infected with Covid-19 [4]. Based on data from the DIY Health Office, there were 1,498 cases of pregnant women who tested positive for Covid-19, and 67 of them died [5].…”
Section: Introductionmentioning
confidence: 99%